The Unhappy Favourite or the Earl of Essex - Banks, John (Columbia University Press, 1939)
Makes available a modern reprint of a good, restoration play with two claims to distinction - It was the first dramatic treatment of the Elizabeth and Essex theme in literature and it set the stage of the she-tragedy as a new type of drama